Aqueous extracts of Portulaca oleracea L. alleviate atopic dermatitis by restoring skin barrier function - Wei, Haobin; Chen, Zhang; Lai, Wenjie; Wang, Wenxian; Bian, Xiqing; Zhang, Limin; Li, Xinzhi (Frontiers in Pharmacology, 2025)
BackgroundPortulaca oleracea L. (PO) is an edible plant with a long medicinal history in traditional Chinese medicine for various inflammatory diseases, including skin disorders such as atopic dermatitis (AD). However, the anti-inflammatory effects and AD-alleviating mechanisms of PO remain unclear.MethodsPO aqueous extract was prepared from a water-soluble portion and then mixed with carbomer to obtain a hydrogel, which provided stable drug permeation and absorption in mouse skin. Amantadine acetate was identified as an abundant ingredient and further predicted to be a Janus kinase 1 (JAK1) inhibitor via molecular binding simulation. Mice with AD, established by repeated sensitization with 2,4-dinitrochlorobenzene (DNCB), were topically treated with PO hydrogel. Aurantiamide acetate was applied to HaCaT keratinocytes prior to inflammatory challenge in the presence or absence of JAK1-siRNA. Transcriptional and translational gene expressions associated with cutaneous inflammation or skin barriers were assessed by qPCR and Western blotting, respectively. Enzyme-linked immunosorbent assays were performed to detect immunoglobulin E and proinflammatory factors in skin tissue or serum. The phosphorylation of JAK1, signal transducer and activator of transcription (STAT)3, and STAT6 in keratinocytes and skin were analyzed by Western blotting.ResultsIn DNCB-sensitized mice, the PO hydrogel ameliorated skin lesions, lowered symptom scores, and reduced epidermal thickness by suppressing proinflammatory factor generation, oxidative stress, and the expression of CD4+. The PO hydrogel promoted the expression of caspase-14 and filaggrin, thereby helping restore skin barrier function in AD. The PO hydrogel and/or aurantiamide acetate inhibited the enzymatic activity of JAK1 and downstream (STAT)3/STAT6 signaling pathways in vitro and in vivo.ConclusionPO significantly ameliorated skin lesions and restored epidermal barrier function in AD mice. This was achieved by suppressing JAK1 enzymatic activity and JAK1-mediated STAT signaling pathways.